Clinical evaluation of injectable platelet-rich fibrin and microneedling for gingival phenotype enhancement: A comparative clinical study - Bhawna Shyamsukha (Bioinformation, 2026)
Thin gingival phenotype increases susceptibility to gingival recession and aesthetic compromise, while predictable minimally invasive approaches for phenotype enhancement remain limited. Sixty adults with thin gingival phenotype (GT